THE INFLUENCE OF LEARNING STRATEGIES AND LEARNING ATTITUDES TOWARDS LEARNING ACHIEVEMENT: (Pengaruh Strategi Pembelajaran dan Sikap Belajar Terhadap Prestasi Belajar) - Jaya, Masjaya; Yahya, Muh. (Uniqbu Journal of Social Sciences, 2022)
This study aims to determine: (1) The effect of learning strategies and learning attitudes simultaneously on social studies learning achievement at SDN 30 Pangkep, (2) The effect of learning strategies on social studies learning achievement at SDN 30 Pangkep, (3) The effect of learning attitudes on social studies learning achievement at SDN 30 Pangkep . This type of quantitative descriptive research. The research population was the entire fifth grade of SDN 30 Pangkep. The sampling technique was purposive sampling, as many as 28 people. Data collection techniques through questionnaires, and documentation. Descriptive and inferential data analysis techniques. The results showed that: (1) there is an effect of learning strategies and learning attitudes simultaneously on social studies learning achievement at SDN 30 Pangkep, where the simultaneous influence contribution is 55.8% and the remaining 44.2% is influenced by other factors, (2) there is an influence of learning strategies on social studies learning achievement at SDN 30 Pangkep, where the better the learning strategies used, the learning achievement will increase, (3) there is an influence of learning attitudes on social studies learning achievement at SDN 30 Pangkep, where the better student attitudes in the implementation of social studies learning , does not have a significant effect on learning achievement.